2018
DOI: 10.1021/acs.est.7b05560
|View full text |Cite
|
Sign up to set email alerts
|

Improving Flue Gas Mercury Removal in Waste Incinerators by Optimization of Carbon Injection Rate

Abstract: This study tested the mercury emission characteristics of six municipal solid waste incinerators (MSWIs) and recommended future mercury control via adjusting operational parameters. The results indicated that over 99% of the mercury in solid wastes ended in fly ash and flue gas, of which 3.3-66.3% was emitted to air through stack gas. Mercury in the stack gas was mainly in the form of oxidized mercury (Hg), the proportion (65.4-89.0%) of which was far higher than previous estimation (15%). Mercury removal effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Likewise, for the analyzed process conditions, the simulation results showed that mercury removal efficiencies higher that 95% can be obtained with activated lignite injection rates above 8 kg/h. These results are also in accordance with several reported studies, which showed that the adsorbent amount available for mercury capture is directly correlated to the mercury removal efficiency in both laboratory-scale and industrial-scale facilities (Ghorishi and Gullett, 1998;Li et al, 2018;Scala, 2001b). In fact, higher adsorbent concentrations in the flue gases are associated to a greater collision probability between the solid reactant and the pollutant, and also a greater surface area available for adsorption.…”
Section: Acid Gases Neutralization and Mercury Removal Stage Modelingsupporting
confidence: 92%
“…Likewise, for the analyzed process conditions, the simulation results showed that mercury removal efficiencies higher that 95% can be obtained with activated lignite injection rates above 8 kg/h. These results are also in accordance with several reported studies, which showed that the adsorbent amount available for mercury capture is directly correlated to the mercury removal efficiency in both laboratory-scale and industrial-scale facilities (Ghorishi and Gullett, 1998;Li et al, 2018;Scala, 2001b). In fact, higher adsorbent concentrations in the flue gases are associated to a greater collision probability between the solid reactant and the pollutant, and also a greater surface area available for adsorption.…”
Section: Acid Gases Neutralization and Mercury Removal Stage Modelingsupporting
confidence: 92%
“…Incineration leads to emissions of metals like mercury [108] and organics like dioxins [18,84,109,166] which are highly toxic. They not only put the people living in the vicinity of incinerators to great risk [28,110] but also cause dispersion of these pollutants far and wide [54].…”
Section: Energy Recovery By Incinerationmentioning
confidence: 99%
“…This problem is being addressed through the development of specific sorbents. [5][6][7] By using regenerable sorbents, the mercury that is retained may be desorbed and condensed to be confined and isolated. The sorbents studied so far for this purpose are mainly metal oxides and porous solids impregnated with noble metals such as gold, silver, palladium and platinum.…”
Section: Introductionmentioning
confidence: 99%